Work Stress, Sleep Disturbances, And Quality Of Life In Working University Students - Khatoon, Haleema; Arshad, Abeeha; Khan, Muhammad Luqman; Noor, Amna; Mustafa, Farwa Mustafa; Tahir, Arhamna Tahir (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The pressure of juggling work responsibilities and academic commitments results in increased stress levels, problems with sleep and sub-optimal quality of life. This study examined the relationship between work-related perceived stress (WRPS), sleep disturbances (SD), and quality of life (QOL) among working university students. A total of 287 working Pakistani students (72 men, 215 women) participated in this study and were selected using a purposive sampling technique. Data were collected using the Perceived Stress Scale (α=0.81), PROMIS Sleep Disturbances Short Form (α=0.88), and Quality of Life Scale-16 (α=0.92). The results showed that WRPS is significantly correlated with SD (r=0.397, p<0.01) and negatively correlated with QOL (r=-0.193, p<0.01). Multiple linear regression analysis reveals that SD and QOL are predictors of WRPS. It also confirms that SD is a significant moderator in WRPS and QOL’s relationship, and the interaction variable (SD_QOL) is also significant. The findings emphasized the importance of balancing work and academics to reduce stress and improve students' overall quality of life. Further research should investigate specific stressors and their impact on sleep disturbances and the quality of life.